The Influence of Temperature - Food Availability on the Shell Growth of Sea Scallop Placopecten magellanicus (Gmelin, 1791) - Adi Santoso (Jurnal Kelautan Tropis, 2016)
A study of the growth of the sea scallop, Placopecten magellanicus, under suspended culture conditions was carried out over a seven month period at a culture site in Graves Shoal, Mahone Bay,Nova Scotia – Canada. Scallop spat were cultivated in pearl nets at a density of 30-35 per net set at four locations corresponding to the surface (7 m) and bottom (14 m) at the outer edge and the center of the site. Shell height was measured at monthly intervals. Environmental conditions represented as temperature and food availability at the surface and bottom over the same period were also monitored. Shell Height growth rate was slightly greater at the surface than at the bottom. At the surface sites growth was greater at the outside (SUROUT) than at the center locations, but at the bottom growth was greater at the centre location (BOTIN). The only significant relationship between shell growth and temperature - food variables was chlorophyll a concentration.Sebuah studi tentang pertumbuhan kerang Placopecten magellanicus, di bawah kondisi budidaya yang dilakukan selama tujuh bulan di Graves Shoal, Mahone Bay, Nova Scotia - Kanada. Kerang dibudidayakan dalam jaring mutiara dengan kepadatan 30-35 per set di empat lokasi yang sesuai dengan permukaan (7 m) dan bawah (14 m) di tepi luar dan pusat Graves Shoal. Ketinggian cangkang diukur pada interval bulanan. Kondisi lingkungan direpresentasikan sebagai suhu dan ketersediaan makanan di permukaan dan bawah selama periode yang sama juga dimonitor. Tingkat pertumbuhan  tinggi cangkang sedikit lebih besar di permukaan daripada di bagian bawah. Pada pertumbuhan situs permukaan lebih besar di luar (SUROUT) daripada di lokasi pusat, tetapi pada pertumbuhan bawah lebih besar di lokasi pusat (BOTIN). Satu-satunya hubungan yang signifikan antara pertumbuhan kulit dan suhu - variabel makanan adalah konsentrasi klorofil.